2003
DOI: 10.1074/jbc.m204591200
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of BRCA1 E3 Ubiquitin Ligase Activity through Direct Interaction with the BARD1 Protein

Abstract: The breast and ovarian cancer-specific tumor suppressor RING finger protein BRCA1 has been identified as an E3 ubiquitin (Ub) ligase through in vitro studies, which demonstrated that its RING finger domain can autoubiquitylate and monoubiquitylate histone H2A when supplied with Ub, E1, and UBC4 (E2). Here we report that the E3 ligase activity of the N-terminal 110 amino acid residues of BRCA1, which encodes a stable domain containing the RING finger, as well as that of the full-length BRCA1, was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
183
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(192 citation statements)
references
References 71 publications
7
183
0
2
Order By: Relevance
“…This appeared to be due to BRCA1 stabilizing the FOXA1 protein, increasing the half-life of this protein. This stabilizing effect of BRCA1 has also been observed for another of the interacting partners of BRCA1, namely BARD1 (Xia et al, 2003). Indeed, decreasing the protein expression of BRCA1 also decreased the expression of FOXA1 protein.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This appeared to be due to BRCA1 stabilizing the FOXA1 protein, increasing the half-life of this protein. This stabilizing effect of BRCA1 has also been observed for another of the interacting partners of BRCA1, namely BARD1 (Xia et al, 2003). Indeed, decreasing the protein expression of BRCA1 also decreased the expression of FOXA1 protein.…”
Section: Discussionsupporting
confidence: 57%
“…Since the effect on protein stability is observed only with a BRCA1 protein having an intact C-terminal BRCT repeat domain, we suggest that the interaction occurs at or near the C-terminus of BRCA1. As a comparison, BARD1 and BRCA1 interact via their N-terminal RING domains, and this interaction and the effect on protein stability is unaffected by C-terminal mutations of BRCA1 (Xia et al, 2003). Indeed, a study has demonstrated that FOXA1 is decreased in BRCA1-mutated breast cancers (van't Veer et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Proteins can be polyubiquitylated through the formation of both K48-and K63-linked poly-Ub chains. Although the heterodimeric E2 Ubc13/Uev1A has been shown to cooperate with certain RING finger E3s (21,44,45) to catalyze the formation of poly-Ub chains linked through K63, UbcH5 and several other E2s have been shown to participate in K48-linked poly-Ub chain formation. K63-linked poly-Ub chains have been implicated in the regulation of target protein activities such as kinase activation (21), which is distinct from the traditional degradative, K48-linked ubiquitylation.…”
Section: Trac-1 Cooperates With Both Ubch5c and Ubc13/uev1a To Catalymentioning
confidence: 99%
“…The deleted domain included the RING domain, which binds to the BARD1 protein and which has ubiquitin ligase activity (Hashizume et al, 2001;Wu-Baer et al, 2003;Xia et al, 2003). We tested whether the ubiquitin ligase function was the critical activity deleted from DN-BRCA1 by generating specific point mutations of critical cysteines.…”
Section: Mutation Of the Amino-terminal Ring Domain Caused Growth Supmentioning
confidence: 99%